2019
DOI: 10.3390/mi10050332
|View full text |Cite
|
Sign up to set email alerts
|

A Nanomechanical Analysis of Deformation Characteristics of 6H-SiC Using an Indenter and Abrasives in Different Fixed Methods

Abstract: The super-precise theory for machining single crystal SiC substrates with abrasives needs to be improved for its chemical stability, extremely hard and brittle. A Berkovich indenter was used to carry out a systematic static stiffness indentation experiments on single crystal 6H-SiC substrates, and then these substrates were machined by utilizing fixed, free, and semi-fixed abrasives, and the nanomechanical characteristics and material removal mechanisms using abrasives in different fixed methods were analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…6 For application, the roughness (Ra) of the substrate is usually required to be below 0.3 nm. 7 The surface flattening technology of silicon carbide materials must be continuously improved to meet the needs of industry development. Typical wafer processing processes include ingot processing, slicing, edging, laser marking, rough grinding, fine grinding, CMP, post-CMP cleaning, inspection, packaging, and other process steps.…”
Section: Ssdmentioning
confidence: 99%
“…6 For application, the roughness (Ra) of the substrate is usually required to be below 0.3 nm. 7 The surface flattening technology of silicon carbide materials must be continuously improved to meet the needs of industry development. Typical wafer processing processes include ingot processing, slicing, edging, laser marking, rough grinding, fine grinding, CMP, post-CMP cleaning, inspection, packaging, and other process steps.…”
Section: Ssdmentioning
confidence: 99%
“…For example, by experimental methods, Ding et al [ 8 ] conducted both ultrasonic-assisted and conventional grinding experiments on the monocrystalline SiC; they discovered that the grinding force, surface roughness, and profile wave height were effectively reduced by the ultrasonic-assisted grinding. Pan et al [ 9 ] performed systematic static stiffness indentation experiments on 6H-SiC ceramics, and machined the workpieces by utilizing fixed, free, and semi-fixed abrasives. Finally, they theoretically analyzed the nanomechanical properties and material removal mechanisms of SiC ceramics.…”
Section: Introductionmentioning
confidence: 99%
“…Goel et al [ 9 ] studied the nanomechanical response of 4H-SiC through a quasi-static nanoindentation test, and the critical shear stress of elastic–plastic transition is about 21 GPa. Pan et al [ 10 ] compared the critical load of elastic–plastic transition between C-face and Si-face in 6H-SiC. The results showed that the elastic–plastic transformation threshold of the Si-face was lower.…”
Section: Introductionmentioning
confidence: 99%